UPTAKE ICT - An erasmus+ project for digital inclusion - Barbas, Maria Potes (2018)
Despite the growth in the use of Internet worldwide, there is still a large amount of people that never used it, even in European countries like Portugal and Italy with 33% and 35% citizens that never used respectively. This project aims to address this problem by engaging synergies of nine partners in four countries (Portugal, Italy, United Kingdom and Germany) whose good practices will be shared and validated by the Science and Technology Foundation in Portugal. This network will work both at local, regional, national and international levels in transversal and trans-sectorial areas, both in terms of the partners involved (academic and enterprise), and in terms of the focus group (Vocational education and training; adult and elderly education with special focus on disadvantaged background citizens) literacy inclusion, re-qualification and employability. The main focus is to attend the info-excluded citizen, mainly the ones with disadvantaged backgrounds, both in social and geographical terms by integrating the ICTs in their lives and to share and spread those good practices either among partners and with the community. To include and train these citizens in Information and communications technologies, educational content was developed in various formats and in three levels of difficulty, hoping to respect the individual way of learning.